2011
DOI: 10.1165/rcmb.2011-0001oc
|View full text |Cite
|
Sign up to set email alerts
|

Radical-Containing Particles Activate Dendritic Cells and Enhance Th17 Inflammation in a Mouse Model of Asthma

Abstract: We identified a previously unrecognized component of airborne particulate matter (PM) formed in combustion and thermal processes, namely, environmentally persistent free radicals (EPFRs). The pulmonary health effects of EPFRs are currently unknown. In the present study, we used a model EPFR-containing pollutant-particle system referred to as MCP230. We evaluated the effects of MCP230 on the phenotype and function of bone marrow-derived dendritic cells (BMDCs) in vitro and lung dendritic cells (DCs) in vivo, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
58
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 27 publications
4
58
1
Order By: Relevance
“…We also observed uptake in several other cell types, including macrophages and fibroblasts (data not shown). In agreement with our previous studies, we found substantial oxidative stress (glutathione depletion, increased GSSG/GSH ratios, and increased 8-IP levels) in cells exposed to EPFR-containing particles (14,15,24). In this study, oxidative stress was observed at a substantially lower dose (20 mg/cm 2 ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We also observed uptake in several other cell types, including macrophages and fibroblasts (data not shown). In agreement with our previous studies, we found substantial oxidative stress (glutathione depletion, increased GSSG/GSH ratios, and increased 8-IP levels) in cells exposed to EPFR-containing particles (14,15,24). In this study, oxidative stress was observed at a substantially lower dose (20 mg/cm 2 ).…”
Section: Discussionsupporting
confidence: 93%
“…The importance of TGF-b in bronchiolar EMT has been shown in recent studies (20,24,52). However, monitoring TGFb in BEAS-2B or neonatal ALI culture supernatants or in vivo at 4 or 7 days after exposure revealed no significant change in TGF-b production before or during EMT (data not shown).…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…The fact that priming DCs with a source of UPM increased the frequency of IL-17A 1 cells concurs with previous studies in mice (31,36) and humans (25,31,37) that identified links between air pollution and IL-17A, albeit in distinct experimental settings. However, in this study, we extend that observation to show that NIST-primed DCs also enhanced the frequency of cells expressing Th17-associated cytokines IL-17F and IL-22, as well as IFN-g, GM-CSF, and granzyme B.…”
Section: Discussionsupporting
confidence: 90%
“…Decreased level or function of GSH in antigen-presenting cells, in which the clearing of free radicals is defective, has been shown to increase the numbers of Th2 cells (Kim et al, 2007;Murata et al, 2002;Peterson et al, 1998). Furthermore, oxidative stress has been also reported to modulate the innate and subsequent adaptive immune responses, contributing to the pathogenesis of allergic diseases (Csillag et al, 2010;Wang et al, 2011).…”
Section: Discussionmentioning
confidence: 99%